2017
DOI: 10.1038/srep46277
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of calculated physicochemical and ADMET properties of protein-protein interaction inhibitors

Abstract: The modulation of PPIs by low molecular weight chemical compounds, particularly by orally bioavailable molecules, would be very valuable in numerous disease indications. However, it is known that PPI inhibitors (iPPIs) tend to have properties that are linked to poor Absorption, Distribution, Metabolism, Excretion and Toxicity (ADMET) and in some cases to poor clinical outcomes. Previously reported in silico analyses of iPPIs have essentially focused on physicochemical properties but several other ADMET paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
116
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(121 citation statements)
references
References 144 publications
0
116
0
1
Order By: Relevance
“…The search for understanding the physicochemical properties of small molecules has greatly increased. The understanding of these properties is necessary in the design of new pharmacological compounds with the ability to bind to various biological targets and present beneficial effects to the body, leading to the discovery of new treatments for diseases of more complex origin, such as Alzheimer’s disease [19] .…”
Section: Discussion / Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for understanding the physicochemical properties of small molecules has greatly increased. The understanding of these properties is necessary in the design of new pharmacological compounds with the ability to bind to various biological targets and present beneficial effects to the body, leading to the discovery of new treatments for diseases of more complex origin, such as Alzheimer’s disease [19] .…”
Section: Discussion / Conclusionmentioning
confidence: 99%
“…It was developed to direct the choice of new drug candidate molecules and was also the pioneer in applying these rules to the drug-likeness profile of a given molecule with its physicochemical properties. According to this rule, for a given molecule to be permeable to cell membranes and also to have easy absorption by means of passive diffusion in the intestinal region, it needs to match the following parameters: LogP≤5; PM≤500; HBA≤ 10 and HBD≤5 [19,23] . And riparin B meets all these requirements, without violation (Log P: 2.77; PM: 285.34; HBA: 4; HBD: 1).…”
Section: Discussion / Conclusionmentioning
confidence: 99%
“…Physicochemical property is an important attribute of a molecule which influences efficacy, safety or metabolism and can be predicted by using Lipinski's rule of five (RO5); molecular mass < 500; hydrogen-bond donors (HBD) < 5; hydrogen-bond acceptors (HBA) < 10; and LogP < 5 [33]. The rule suggests that molecules, whose properties fell outside some of these boundaries, would be unlikely to become an orally bioavailable drug [34].…”
Section: Physicochemical Evaluation Of Three Molecules With Highest Bmentioning
confidence: 99%
“…The ADMET/pharmacokinetic properties assessments were carried out using combined Simulation Plus ADMET Predictor™ 9.0 [33] and Swiss ADME tool with a proficient method of Brain Or IntestinaL EstimateD permeation method (BOILED-Egg) [38]. The obtained results for ADMET/pharmacokinetic properties presented in Table 7 revealed that all the selected molecules possessed the attribute for central nervous system (CNS) blood-brain barrier (BBB) penetration and with high gastrointestinal (GI) absorption in comparison with their Log BB values.…”
Section: Admet/pharmacokinetic Properties Of the Selected Three Molecmentioning
confidence: 99%
See 1 more Smart Citation